2000
DOI: 10.1097/00007632-200005150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Thoracic and Lumbar Vertebrae in Idiopathic Scoliosis

Abstract: The morphometry in scoliotic vertebrae is substantially different from that of vertebrae in normal spines, with an asymmetrical intravertebral deformity shown in scoliotic vertebrae. Pedicle screw instrumentation on the concavity in the apical region of thoracic curves appears critical because of the small endosteal pedicle width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
1
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(154 citation statements)
references
References 28 publications
12
129
1
12
Order By: Relevance
“…Because the clinical definition of scoliosis as a lateral curve with a Cobb angle > 10° is not applicable to a palaeoanthropological context, the present study uses a morphometric approach similar to that of Liljenqvist et al (2000) and Parent et al (2002;2004a, b) to evaluate the rotational deformity of scoliotic vertebrae. Our results confirm that scoliotic spines can be distinguished from non-scoliotic vertebral columns by a combination of different asymmetries of the individual vertebrae that increase towards the apex of the curve, but are absent at the neutral vertebra.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the clinical definition of scoliosis as a lateral curve with a Cobb angle > 10° is not applicable to a palaeoanthropological context, the present study uses a morphometric approach similar to that of Liljenqvist et al (2000) and Parent et al (2002;2004a, b) to evaluate the rotational deformity of scoliotic vertebrae. Our results confirm that scoliotic spines can be distinguished from non-scoliotic vertebral columns by a combination of different asymmetries of the individual vertebrae that increase towards the apex of the curve, but are absent at the neutral vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…1). Morphometric studies further demonstrated a decreased pedicular width on the concavity of the curve, increased lateral wedging of the vertebral bodies towards the apex of the curve, and facet surface asymmetries (Liljenqvist et al, 2000;Parent et al, 2002;Parent et al, 2004b).…”
Section: Scoliosismentioning
confidence: 94%
See 1 more Smart Citation
“…Pedicle screw fixation can be dangerous because of the maximum permissible translational error of less than 1 mm and rotational error of less than 5° [16] in the scoliotic spine, especially the mid-thoracic spine because of the small pedicle diameter, limited space between the spinal cord and the medial pedicle, and the morphological deformity of the pedicle [17]. A freehand thoracic pedicle screw insertion technique with no radiographic guidance or intraoperative tracking devices has been reported to be safe and reliable [15].…”
Section: Discussionmentioning
confidence: 99%
“…The anatomies of vertebrae and pedicle are also distorted in patients with neuromuscular scoliosis like idiopathic scoliosis [28,43]. Pedicle screw fixation in such patients is difficult, so accurate and safe placement is mandatory to achieve the fixation [33].…”
Section: Introductionmentioning
confidence: 99%